Optimizing Registration of Halal Certification for Local MSMEs in Ciburial Village, Indonesia - Mafruhat, Ade Yunita; Haryatiningsih, Ria; Haviz, Meidy; Nurrahman, Ahmad Arif; Arif, Muhammad Fauzi; Sabilillah, Ghirah Jihad Fie; Prameswari, Khofifah Alya; Kiransyah, Muhammad Rafky Razif; Lesmana, Lovie Dwifany (KnE Social Sciences, 2024)
This article aims to measure the effectiveness of business legality community service activities (PKM) through the socialization and assistance of Halal Certification in Ciburial Village. This effectiveness is demonstrated by increasing the knowledge and awareness of MSMEs in legalizing the leading product micro, small and medium enterprises (MSMEs) – Ciburial Village. Based on the results of discussions with the Ciburial Village, one of the problems of Ciburial Village MSMEs is the lack of motivation in legalizing MSMEs to increase the competitiveness of Village MSMEs products. Implementation methods used include field surveys, socialization, mentoring, distributing questionnaires, different tests, documentation, and preparation of the final report. The measurement results showed that this PKM activity is very effective with an effectiveness value of 94.18. The effectiveness of this activity was also strengthened by the results of PKM activities which showed that there were differences in knowledge and awareness before and after the activity. This difference is indicated by the results of the different tests where Sig. (2-Mean Std. tailed) < 0.1. This means that PKM has succeeded in increasing the awareness of MSMEs to register their products for halal certification. Keywords: competitiveness, halal certification, village leading MSMEs